The use of inertial measurement units to quantify forearm loading and symmetry during gymnastics vault training sessions. Issue 2 (1st February 2023) - Campbell, Rhiannon A.; Bradshaw, Elizabeth J.; Ball, Nick; Hunter, Adam; Spratford, Wayne
ABSTRACT: The upper limbs are important in gymnastics vaulting, as the success of the flight phase is dependent on a quick and forceful push-off from the vault. This places the upper limbs under stress, which has been associated with pain and injury. This study aimed to quantify forearm segmental loading and symmetry when performing foundation to advanced-level vaulting skills during training. Twelve advanced-level artistic gymnasts (female, n = 6; male, n = 6) wore bilaterally forearm-mounted inertial measurement units while completing their vaulting sessions. The peak resultant acceleration for the leading and non-leading forearms during contact were calculated. Female gymnasts performed variations of Yurchenko vaults, while male gymnasts performed Handspring and Tsukahara vaults. Descriptive statistics (median and inter-quartile range), symmetry index scores, and total session impact load (measure of cumulative loading) were calculated between the lead and non-lead forearms. High asymmetrical loading was identified for some Yurchenko, Handspring, and Tsukahara vaults, with large variations identified between gymnasts. Some gymnasts experienced greater loading at their lead forearm, while others experienced greater loading at their non-lead forearm. Results indicate that limb loading patterns in advanced gymnastics are highly individualised, indicating that individual analysis is needed to identify gymnasts (or limbs) at an increased risk for overuse injury.